Duodenal microflora in infants with acute and persistent diarrhoea. Issue 5 (May 1983) - Hill, I D; Mann, M D; Moore, L; Bowie, M D
Abstract : The duodenal bacterial population was determined qualitatively and quantitatively in 3 groups of infants with diarrhoeal disease of varying duration. Infants with acute self limiting diarrhoea (group 1) had an abnormal overgrowth of organisms in the upper small bowel which was similar to that found in infants whose diarrhoea persisted after 4 days in hospital (group 2). The total duodenal organism count in infants with diarrhoea persisting after 7 days in hospital (group 3) was almost 100 times greater than either of the other groups. The findings may have important implications in preventing persistent diarrhoea from becoming protracted.